Heterologous constitutive production of short-chain-length polyhydroxyalkanoates in Pseudomonas putida KT2440: the involvement of IbpA inclusion body protein - Manoli, Maria-Tsampika; Blanco, Francisco G.; Rivero-Buceta, Virginia; Kniewel, Ryan; Alarcon, Sandra Herrera; Salgado, Sergio; Prieto, M. Auxiliadora (Frontiers in Bioengineering and Biotechnology, 2023)
Designing cell factories for the production of novel polyhydroxyalkanoates (PHAs) via smart metabolic engineering is key to obtain à la carte materials with tailored physicochemical properties. To this end, we used the model medium-chain-length-PHA producing bacterium, Pseudomonas putida KT2440 as a chassis, which is characterized by its metabolic versatility and stress tolerance. Different PHA biosynthetic modules were assembled in expression plasmids using the Golden gate/MoClo modular assembly technique to implement an orthogonal short-chain-lengh-PHA (scl-PHA) switch in a "deaf" PHA mutant. This was specifically constructed to override endogenous multilevel regulation of PHA synthesis in the native strain. We generated a panel of engineered approaches carrying the genes from Rhodospirillum rubrum, Cupriavidus necator and Pseudomonas pseudoalcaligenes, demonstrating that diverse scl-PHAs can be constitutively produced in the chassis strain to varying yields from 23 to 84% PHA/CDW. Co-feeding assays of the most promising engineered strain harboring the PHA machinery from C. necator resulted to a panel of PHBV from 0.6 to 19% C5 monomeric incorporation. Chromosomally integrated PHA machineries with high PhaC Cn synthase dosage successfully resulted in 68% PHA/CDW production. Interestingly, an inverse relationship between PhaC synthase dosage and granule size distribution was demonstrated in the heterologous host. In this vein, it is proposed the key involvement of inclusion body protein IbpA to the heterologous production of tailored PHA in P. putida KT2440.